2015
DOI: 10.1002/ajmg.a.36879
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of invdupdel(8p) rearrangement: Clinical, cytogenetic and molecular characterization

Abstract: Inverted duplication 8p associated with deletion of the short arms of chromosome 8 (invdupdel[8p]) is a relatively uncommon complex chromosomal rearrangement, with an estimated incidence of 1 in 10,000-30,000 live borns. The chromosomal rearrangement consists of a deletion of the telomeric region (8p23-pter) and an inverted duplication of the 8p11.2-p22 region. Clinical manifestations of this disorder include severe to moderate intellectual disability and characteristic facial features. In most cases, there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 24 publications
3
39
0
Order By: Relevance
“…In the present case, the deletion/duplication did not include the GATA4 gene; however, the duplication size was one of the largest that has ever been reported. Two previous studies reported a correlation between increased duplication length and severity of cognitive deficits [Fisch et al, ; García‐Santiago et al, ]. In this case, we can speculate that large duplication length may be associated with CHD that was uncharacteristically severe for this disorder.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In the present case, the deletion/duplication did not include the GATA4 gene; however, the duplication size was one of the largest that has ever been reported. Two previous studies reported a correlation between increased duplication length and severity of cognitive deficits [Fisch et al, ; García‐Santiago et al, ]. In this case, we can speculate that large duplication length may be associated with CHD that was uncharacteristically severe for this disorder.…”
Section: Discussionsupporting
confidence: 56%
“…Invdupdel[8p] is a well‐described and uncommon chromosomal rearrangement with an incidence rate of around 1 in 10,000–30,000 liveborn infants [García‐Santiago et al, ]. In this case, we present the first known prenatal diagnosis of an invdupdel[8p] syndrome complicated with polyvalvuvar dysplasia and central nervous system (CNS) abnormalities.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The parental karyotype and chromosomal microarray results were normal. The 8p inverted duplication and deletion were associated with congenital heart disease, a hypoplastic corpus callosum, facial dysmorphisms, intellectual disability, autism, hypotonia, and epilepsy . Termination of pregnancy was performed at 23 weeks.…”
Section: Case Descriptionsmentioning
confidence: 99%
“…2). Actually, a previous patient's rearrangement [9] resulted from a mechanism seemingly unrelated to OR clusters. In another subject, the reportedly inverted 8p duplication was not proven [7], and in still another [8], there was an 8p triplication instead of duplication.…”
mentioning
confidence: 99%